A State-space Approach for MIMO Channel Tracking in SC-FDE Transmissions - Pedrosa, P.; Castanheira, D.; Silva, A.; Dinis, R.; Gameiro, A. (IEEE Vehicular Technology Conference, 2020)
In this paper we consider a multi-input multi-output (MIMO) channel subject to time variations. These channel variations are due to the presence of a Doppler term which imposes a phase rotation on the original channel impulse response (CIR). On one hand, modern equalization schemes require the knowledge of the CIR or, equivalently, the channel frequency response (CFR). On the other hand, channel estimation procedures consume significant resources, particularly when transmitting training sequences. Therefore, we propose the use of a statespace approach, namely the extended Kalman filter (EKF), to interpolate the channel estimates obtained during the training stage onto the data transmission stage. Our approach is validated considering single-carrier frequency-domain equalization (SCFDE) transmissions.